A Bird is Known by its Flight: An Exploration of the Geostrategic Relationship Between the United States and Uzbekistan Since the War on Terror - Blau, Michelle (Auckland University of Technology, 2015)
This thesis is a contribution to the foreign policy discourse on the tension between defense and human rights in Central Asia over the past decade. This qualitative case study uses process tracing to explore how the need for cooperation on the War on Terror in Afghanistan affected US Government criticism of human rights abuses committed by its ally, Uzbekistan. The case study will demonstrate that the US was willing to remain a passive observer of human rights violations in Uzbekistan, provided the Government of Uzbekistan would cooperate with US geopolitical interests in the War on Terror.
Keywords: Geopolitics; Uzbekistan; War on terror; Human rights; Post Soviet; Civil and political rights